Role of Traditional Chinese Medicine in Bone Regeneration and Osteoporosis - Peng, Zhicai; Xu, Ronghua; You, Qinjian (Frontiers in Bioengineering and Biotechnology, 2022)
According to WHO, osteoporosis is a systematic bone disability marked by reduced bone mass and microarchitectural degeneration of osseous cells, which leads to increased bones feebleness and fractures vulnerability. It is a polygenetic, physiological bone deformity that frequently leads to osteoporotic fractures and raises the risk of fractures in minimal trauma. Additionally, the molecular changes that cause osteoporosis are linked to decreased fracture repair and delayed bone regeneration. Bones have the ability to regenerate as part of the healing mechanism after an accident or trauma, including musculoskeletal growth and ongoing remodeling throughout adulthood. The principal treatment approaches for bone loss illnesses, such as osteoporosis, are hormone replacement therapy (HRT) and bisphosphonates. In this review, we searched literature regarding the Traditional Chinese medicines (TCM) in osteoporosis and bone regeneration. The literature results are summarized in this review for osteoporosis and bone regeneration. Traditional Chinese medicines (TCM) have grown in popularity as a result of its success in curing ailments while causing minimal adverse effects. Natural Chinese medicine has already been utilized to cure various types of orthopedic illnesses, notably osteoporosis, bone fractures and rheumatism with great success. TCM is a discipline of conventional remedy that encompasses herbal medication, massage (tui na), acupuncture, food, and exercise (qigong) therapy. It is based on more than 2500 years of Chinese healthcare profession. This article serves as a comprehensive review summarizing the osteoporosis, bone regeneration and the traditional Chinese medicines used since ancient times for the management of osteoporosis and bone regeneration.